2018
DOI: 10.1111/jipb.12674
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of species boundaries in three sympatricLigularia(Senecioneae, Asteraceae) species

Abstract: The key process in speciation concerns the formation and maintenance of reproductive isolating barriers between diverging lineages. Although species boundaries are frequently investigated between two species across many taxa, reproductive isolating barriers among multiple species (>2) that would represent the most common phenomenon in nature, remain to be clarified. Here, we use double digest restriction-site associated DNA (ddRAD) sequencing to examine patterns of hybridization at a sympatric site where three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 65 publications
2
9
0
Order By: Relevance
“…The extent to which natural hybridization contributes to evolution is wide‐ranging (Barton ; Paun et al ; Whitney et al ; Abbott et al ; Abbott and Brennan ; Schumer et al ; Pfennig et al ). Numerous studies have long revealed that the outcomes of mating between closely related species can either result in the total breakdown of species barriers and homogenize parental genomes (Dobzhansky et al ), or facilitate the formation of stable hybrid zones which maintain species barriers with or without gene introgression (Anderson ; Xie et al ; Zhang et al ). Alternatively, such mating could allow for the establishment of novel gene combinations in hybrids that can enhance evolutionary responses to selection, through local adaptation, and lead to the formation of new species (Anderson and Stebbins ; Levin ; Harrison ; Vallejo‐Marín et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The extent to which natural hybridization contributes to evolution is wide‐ranging (Barton ; Paun et al ; Whitney et al ; Abbott et al ; Abbott and Brennan ; Schumer et al ; Pfennig et al ). Numerous studies have long revealed that the outcomes of mating between closely related species can either result in the total breakdown of species barriers and homogenize parental genomes (Dobzhansky et al ), or facilitate the formation of stable hybrid zones which maintain species barriers with or without gene introgression (Anderson ; Xie et al ; Zhang et al ). Alternatively, such mating could allow for the establishment of novel gene combinations in hybrids that can enhance evolutionary responses to selection, through local adaptation, and lead to the formation of new species (Anderson and Stebbins ; Levin ; Harrison ; Vallejo‐Marín et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Many empirical studies have focused on the onset of natural hybridization and have examined issues including reproductive barriers [5,6], backcrossing and introgression which are sometimes involved in transference of adaptation [7][8][9] or acceleration of extinction by genetic swamping [10][11][12]. A phenomenon previously assumed to be rare but recently found to be common, is the presence of hybrids consisting mainly of F 1 s [13][14][15][16][17], due to intrinsic incompatibilities including F 1 hybrid sterility and/or inviability [4,13,18], and extrinsic selection, with other genotypes of hybrids being outcompeted due to strong habitat selection [13,14,19,20]. A certain amount of habitat disturbance may be able to promote the occurrence of natural hybridization [21][22][23], as on the one hand it breaks the original existence of ecological isolation between species and promotes hybridization, and on the other hand it also provides suitable habitat for hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…For the most part, studies reveal that when two or more closely related species are in sympatry, hybridization frequently occurs and natural hybrid zones are likely to form (e.g. [ 15 , 17 , 18 ]).…”
Section: Introductionmentioning
confidence: 99%